'Curiouser and curiouser!': Organizations as Wonderland – a metaphorical alternative to the rational model. (April 2016) - McCabe, Darren
The metaphors in Morgan's (1986) Images of Organization largely imply order, rationality, stability and manageability. This reflects that the text is concerned with facilitating the design and management of organizations. This article draws on Lewis Carroll's (1865) novel Alice's Adventures in Wonderland to propose Wonderland as an alternative metaphor that places at centre stage issues such as absurdity, irrationality, uncertainty and disorder. Rather than a marginal or temporary aberration, it is argued that such conditions need to be understood as an everyday experience for many. This metaphor is important because those who are tasked with managing organizations may find it stressful and puzzling that they are so inept, when they compare their experiences and achievements with the rational model. In this sense, it offers both comfort and perhaps encouragement, but it should also foster humility and caution in terms of what those at the top can achieve. Likewise, those on the receiving end of irrational decisions or who reside in absurd worlds can gain solace from knowing that they are not alone, whilst those concerned with resisting such conditions can find strength in the knowledge that those in positions of authority are not omniscient/omnipotent.